2016
DOI: 10.5194/piahs-373-45-2016
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir impacts downstream in highly regulated river basins: the Ebro delta and the Guadalquivir estuary in Spain

Abstract: Abstract. Regulation by reservoirs affects both the freshwater regime and the sediment delivery at the area downstream, and may have a significant impact on water quality in the final transitional water bodies. Spain is one the countries with more water storage capacity by reservoirs in the world. Dense reservoir networks can be found in most of the hydrographic basins, especially in the central and southern regions. The spatial redistribution of the seasonal and annual water storage in reservoirs for irrigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…From the analysis of washover dimensions and morphologies, and based on the proposal by Matias et al [8], it can be concluded that the main cause of washover generation is structural erosion [39]. This, together with a lack of sediment derived in large part from heavy dam constructions in the rivers that nourish the SW coast of the Iberian Peninsula [54,55], can hinder dune recovery, and it is linked to a long-term erosion trend. Evidence of this sediment shortage includes the nourishment works performed at Camposoto over recent decades [35], as well as the outcropping of the fossil salt marsh layers of the foreshore (Figure 12), like the episodes described by Burningham [18] and Davis and Fitzgerald [19] in similar spit-barrier systems.…”
Section: Discussionmentioning
confidence: 99%
“…From the analysis of washover dimensions and morphologies, and based on the proposal by Matias et al [8], it can be concluded that the main cause of washover generation is structural erosion [39]. This, together with a lack of sediment derived in large part from heavy dam constructions in the rivers that nourish the SW coast of the Iberian Peninsula [54,55], can hinder dune recovery, and it is linked to a long-term erosion trend. Evidence of this sediment shortage includes the nourishment works performed at Camposoto over recent decades [35], as well as the outcropping of the fossil salt marsh layers of the foreshore (Figure 12), like the episodes described by Burningham [18] and Davis and Fitzgerald [19] in similar spit-barrier systems.…”
Section: Discussionmentioning
confidence: 99%
“…The estuary is tidal, with the behaviour of the river discharge and the renewal of the estuarine water jointly determined by the tidal and neighbouring coastal currents (Ojeda et al, 1995). Finally, the GD river has a length of 657 km and a drainage area of about 57,400 km 2 (Polo et al, 2016). Its current mean discharge rate is 90 m 3 s À1 , with a marked interannual variability (see Fig.…”
Section: Study Regionmentioning
confidence: 99%
“…Since the 1990s, increasing demands for irrigation, municipal water consumption, and critical environmental flow for conserving wildlife habitats in the context of climate change have challenged water resource management in the basin. Thus, there is an urgent need to reliably simulate water cycling in the basin to provide a solid basis for policy formulation and management actions which strive to achieve a balance among water demands for different purposes (Poff et al, 2003).…”
Section: Introductionmentioning
confidence: 99%